2021
DOI: 10.1016/j.heliyon.2021.e06453
|View full text |Cite
|
Sign up to set email alerts
|

Good corporate governance and corporate sustainability performance in Indonesia: A triple bottom line approach

Abstract: This study aims to investigate the effect of good corporate governance (GCG) on corporate sustainability performance (CSP) using the Triple Bottom Line (TBL) approach in a two-tier GCG system. GCG is measured by the size and education background of board of commissioners (BoC) and top management team (TMT). CSP consists of economic, social, and environment sustainability performance. As many as 117 sample data were collected from the financial statements, annual reports and sustainability reports of non-financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 104 publications
2
60
0
8
Order By: Relevance
“…These studies have presented relevant evidence on the impacts of I4.0 on CS. However, this topic offers research opportunities because many companies still face difficulties in developing and operationalizing sustainability (Tjahjadi et al, 2021). This has been corroborated by Ejsmont et al (2020), who, when performing a bibliometric analysis to verify the impacts of I4.0 on CS, found that, although the literature provides an essential contribution to this field of knowledge, no studies were identified that presented propositions that should be adopted during the transition process to a sustainable business model via I4.0.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These studies have presented relevant evidence on the impacts of I4.0 on CS. However, this topic offers research opportunities because many companies still face difficulties in developing and operationalizing sustainability (Tjahjadi et al, 2021). This has been corroborated by Ejsmont et al (2020), who, when performing a bibliometric analysis to verify the impacts of I4.0 on CS, found that, although the literature provides an essential contribution to this field of knowledge, no studies were identified that presented propositions that should be adopted during the transition process to a sustainable business model via I4.0.…”
Section: Introductionmentioning
confidence: 95%
“…These studies have presented relevant evidence on the impacts of I4.0 on CS. However, this topic offers research opportunities because many companies still face difficulties in developing and operationalizing sustainability ( Tjahjadi et al., 2021 ). This has been corroborated by Ejsmont et al.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability performance of a company is usually measured through the triple bottom line (TBL), which refers to the accounting of financial, social, and environmental variables [65]. Every topic belonging to each of these three sustainability dimensions can be converted into a distinct sustainability data item [66] by referring to sustainability accounting.…”
Section: Sustainability Data Reporting and Digital Toolsmentioning
confidence: 99%
“…Currently, Indonesia is making an acceleration in producing agricultural products that are safe and free from residues. One of them is through Good Corporate Governance, which has implications for sustainable corporate performance, which has four essential values: economic sustainability performance, environmental sustainability performance, and social sustainability performance 17 .…”
Section: Introductionmentioning
confidence: 99%